Introduction [in Securing food for all in Bangladesh] - Ahmed, Akhter; Islam, Nurul; Mujeri, Mustafa K. (University Press Limited, 2021)
Food is the most important basic need for sustenance and survival, and the right to food is among the fundamental human rights. Access to sufficient food at all times to meet dietary needs of millions of people in Bangladesh is a matter of critical importance and should be an issue of paramount concern to those responsible for the nation’s welfare. According to Article 15 (a) of the Constitution of the People’s Republic of Bangladesh, it is a principal responsibility of the State to meet the basic food needs of all citizens. Furthermore, Article 18(1) of the Constitution has made the improvement of the nutritional status of the people and the improvement of public health, the primary responsibilities of the state. This book assembles a set of papers that collectively focus on the extensive undertaking of securing food for all in Bangladesh. The book addresses four broad issues: (1) agricultural technology adoption; (2) input use and agricultural productivity; (3) food security and output market; and (4) poverty, food security and women’s empowerment. The chapters, fifteen in total, address diverse aspects within these four themes.